Pedagogic content knowledge (PCK) in teacher competence development - Zaenal Abidin; Anna Fitri Hindriana; Asep Ginanjar Arip (Community Empowerment, 2023)
The teacher competency needed when carrying out professional duties in front of the class is Pedagogical Content Knowledge (PCK). One of the PCK competencies needed by teachers today is to have learning strategies according to the topic and students' conditions. In connection with this, the Kuningan University Postgraduate School, in collaboration with the Kuningan Regency Science Subject Teachers' Conference, held a Teacher Competency Improvement Workshop. The methods used in this workshop are lectures, question and answer sessions, and assignment methods. The results obtained from holding this workshop were an increase in participants' competence in packaging learning material that was easy for students to understand and appropriate for the students' conditions. This can be seen from the increase in pre-test results (mean = 0.61) to post-test PCK (mean = 61.38), indicating a rise of 40.49. Participants also increasingly understand how to package teaching materials so that they are easily understood by students and suitable for the students' conditions. This is evident when participants are given the task of completing several case examples, including those related to choosing learning strategies according to variations in topics and student conditions. Based on this, PCK training through workshops can be a solution for teacher professional development.